Quality Management In Implementation At Santo Mikael Christian Middle School, Cimahi City - Kurniati, Tetty; Firdaus, Erwin; Jubaedah, Edah (Yayasan Azka Hafidz Maulana, 2023)
Quality management is very important in improving the quality of education in junior high schools (JHC) in Indonesia. In this article, research on quality management at Santo Mikael Christian Middle School in Cimahi is conducted to gain a better understanding of best practices, barriers, and opportunities that can improve the quality of education at the junior high school level. This study aims to determine the planning, implementation, monitoring, and evaluation of quality management in the JHC, as well as the constraints faced and improvement efforts made. The results of this study are expected to provide valuable insights for teachers, parents and the community in supporting school performance improvement through quality management. In this study, a qualitative method was used with a case study type and data collection techniques in the form of observation, interviews, and literature study. The findings of this study indicate that Santo Mikael Christian Middle School has implemented various standards of good management, such as program planning, student management, teacher and educational staff utilization, facility and infrastructure management, financing management, and creating a conducive atmosphere and environment. However, there is still a gap between the actual conditions of the school and the expected ideal conditions. Therefore, it is important for schools to continue to plan, implement, monitor and evaluate well and implement effective quality management to reduce these gaps